SUSTAINABLE TOURISM STRATEGIES THROUGH MAPPING DISASTER-PRONE TOURISM AREAS IN SITUBONDO REGENCY, INDONESIA - Rois Dinan; Muhammad Yahya; Asya Karima; Mardia Husdir; Nurul Rahma (Politeknik Pariwisata Makassar, 2025)
Tourism development in disaster-prone areas presents both opportunities and risks that demand careful spatial planning and sustainable management. Situbondo Regency, located in East Java, Indonesia, offers diverse natural attractions ranging from coastal landscapes and mountain ecosystems to conservation areas. However, the regency’s geographical characteristics also expose many of its tourism destinations to hazards such as floods, landslides, earthquakes, volcanic activity, and coastal abrasion. This study aims to map tourism areas identified in the Regional Spatial Plan (RTRW) of Situbondo and examine their overlap with disaster-prone zones as a foundation for developin2g strategies toward sustainable tourism. A spatial analysis approach was employed by overlaying designated tourism zones with hazard-prone maps derived from official planning documents and secondary data. The results indicate that several key tourism sites, particularly those situated along coastal corridors and volcanic slopes, fall within medium to high disaster risk areas. These findings underscore the urgency of integrating disaster risk reduction measures into tourism development and policy implementation. The study suggests that sustainable strategies should emphasize infrastructure resilience, the incorporation of disaster-sensitive design principles, and the reinforcement of local community capacity in preparedness and response. In addition, diversification of tourism products that reduce environmental vulnerability, improved early warning systems, and stronger risk communication with stakeholders are essential for minimizing potential losses. Aligning spatial planning instruments with sustainable tourism frameworks is also crucial to ensure long-term destination resilience. This research highlights the importance of disaster-aware tourism planning in Situbondo Regency. By integrating spatial planning, disaster risk management, and sustainability principles, Situbondo can strengthen the safety of its destinations, maintain ecological integrity, and enhance the resilience of its tourism sector in the face of natural hazards.